Regulatory Roles of Conserved Intergenic Domains in Vertebrate Dlx Bigene Clusters - Ghanem, Noël (Cold Spring Harbor Laboratory Press, 2003)
Dlx homeobox genes of vertebrates are generally arranged as three bigene clusters on distinct chromosomes. The Dlx1/Dlx2, Dlx5/Dlx6, and Dlx3/Dlx7 clusters likely originate from duplications of an ancestral Dlx gene pair. Overlaps in expression are often observed between genes from the different clusters. To determine if the overlaps are a result of the conservation of enhancer sequences between paralogous clusters, we compared the Dlx1/2 and the Dlx5/Dlx6 intergenic regions from human, mouse, zebrafish, and from two pufferfish, Spheroides nephelus and Takifugu rubripes. Conservation between all five vertebrates is limited to four sequences, two in Dlx1/Dlx2 and two in Dlx5/Dlx6. These noncoding sequences are >75% identical over a few hundred base pairs, even in distant vertebrates. However, when compared to each other, the four intergenic sequences show a much more limited similarity. Each intergenic sequence acts as an enhancer when tested in transgenic animals. Three of them are active in the forebrain with overlapping patterns despite their limited sequence similarity. The lack of sequence similarity between paralogous intergenic regions and the high degree of sequence conservation of orthologous enhancers suggest a rapid divergence of Dlx intergenic regions early in chordate/vertebrate evolution followed by fixation of cis-acting regulatory elements. [Supplemental material is available online at www.genome.org.]